PENGARUH PENDEKATAN STUDENT CENTERED APPROACH TERHADAP KEAKTIFAN DAN HASIL BELAJAR SENI RUPA DI SMPN 10 PADANG - Susi Susanti; Yusron Wikarya (Serupa The Journal of Art Education, 2020)
Thist study aims to iinvestigate the difference of the activeness and learning outcomes between students treated with Student Centered Approach (SCA) Approach and students treated with  Conventional Learning strategy in Fine Arts learning at SMP Negeri 10 Padang. It was a quantitative research with quasiexperimental form (Quasi Experiment). The results showedt that there were differencesi on the activeness and learning outcomes between students treated with Student Centered Approach (SCA) Approach andt students treated with Conventional Learning  strategy with a significance level of 0,000 <0.05. Thus, it cant be concluded thatt the use of  Student Centered Approach affects the activeness and learning outcomes of students.Kata kunci: Seni Rupa, Pendekatan Pembelajaran, Student Centered Approach, Keaktifan, Hasil Belajar